A new ratiometric AIE fluorescent probe for detecting cysteine in food samples and imaging in the biological system. (30th January 2023) - Gong, Shuai; Qin, Ahui; Zhang, Yan; Li, Mingxin; Chen, Xiaoyi; Liang, Yueyin; Xu, Xu; Wang, Zhonglong; Wang, Shifa
Graphical abstract: Highlights: A ratiometric fluorescent probe NFA with AIE property for the determination of Cys was developed. The probe NFA showed sensitive (0.21 μM), rapid (within 2 min) response to Cys and could distinguish Cys from Hcy and GSH. Probe NFA was used for the detection of Cys in real food samples. Probe NFA has been successfully applied to visualize endogenous and exdogenous Cys in living HeLa cells and zebrafish. Abstract: l -Cysteine (Cys) plays a vital part in the food industry and biological processes. Herein, a novel ratiometric fluorescent probe NFA with aggregation-induced emission (AIE) property was developed to discriminate Cys from Hcy and GSH. The probe showed a ratiometric fluorescence response to Cys with the emission wavelength shifted from 450 nm to 495 nm. Probe NFA possessed good advantages in the detection of Cys including wide linear range (0–100 μM), low detection limit (0.21 μM), and rapid response time (within 2 min). Compared with previous reports, this is the first ratiometric probe that achieves the quantitative detection of Cys in different food samples in real-time (cabbage, bamboo shoots, lotus root, garlic, apple, pear, milk powder, and liquid milk). Moreover, NFA is successfully applied for ratiometric image endogenous and exogenous Cys in HeLa cells and zebrafish which demonstrated its practical biological application.